Acceptability of passion fruit (passiflora edulis linn.) in making jam - Amurao, Rosel R.; Curatcha, Jennylyn A.; Lee, Julian B.; Samson, John Carlo A. (2013)
'The study focused on the Acceptability of Passion Fruit in Making Jam wherein descriptive method of research and one shot experimental study were used. The developed product was prepared using Passion Fruit as the main ingredients in making Jam." -- Abstract
Undergraduate thesis (Hotel and Restaurant Management) - University of Rizal System, Cainta 2013
Includes bibliographical references.
Amurao, R. R., [and three others]. (2013). Acceptability of passion fruit (passiflora edulis linn.) in making jam. University of Rizal System.
In English text.
Keywords: Hotel and Restaurant Management -- Thesis, Academic